2020
DOI: 10.1063/5.0018962
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of stochastic Størmer–Verlet thermostats generating correct statistics

Abstract: In light of the recently developed complete GJ set of single random variable stochastic, discrete-time Størmer–Verlet algorithms for statistically accurate simulations of Langevin equations [N. Grønbech-Jensen, Mol. Phys. 118, e1662506 (2020)], we investigate two outstanding questions: (1) Are there any algorithmic or statistical benefits from including multiple random variables per time step and (2) are there objective reasons for using one or more methods from the available set of statistically correct algor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…It is worth clarifying that the use of the second, independent noise contribution β n+ 1 2 within the time step is exclusively for the half-step velocity, and it is therefore not in conflict with the result of Ref. [34], stating that there can only be one stochastic variable per time step for the configurational coordinate r n to be statistically correct. We notice that this new half step velocity coincides with the previously identified statistically correct half-step velocity for the GJ-III method, where c 3 = 1 [29] (see also Eq.…”
Section: A Half-step Velocitiesmentioning
confidence: 89%
See 4 more Smart Citations
“…It is worth clarifying that the use of the second, independent noise contribution β n+ 1 2 within the time step is exclusively for the half-step velocity, and it is therefore not in conflict with the result of Ref. [34], stating that there can only be one stochastic variable per time step for the configurational coordinate r n to be statistically correct. We notice that this new half step velocity coincides with the previously identified statistically correct half-step velocity for the GJ-III method, where c 3 = 1 [29] (see also Eq.…”
Section: A Half-step Velocitiesmentioning
confidence: 89%
“…The configurational sampling is, however, not limited by the additivity of the O operation, since Ref. [34] has shown that no stochastic Verlet-type integrator can produce correct Boltzmann statistics with more than one independent stochastic number contributing to the configurational equation per time step. If O were not at the pivotal (i.e., central) position, but instead used as two symmetrically positioned 1 2 ∆t operations, then the configurational variable r n+1 would be subject to two separate stochastic contributions, σ n + and σ n+1 − .…”
Section: Generalized Splittingmentioning
confidence: 99%
See 3 more Smart Citations